Studies of the catabolic pathway of degradation of nitrobenzene by Pseudomonas pseudoalcaligenes JS45: removal of the amino group from 2-aminomuconic semialdehyde. - He, Z (1997)
Pseudomonas pseudoalcaligenes JS45 utilizes nitrobenzene as the sole source of nitrogen, carbon, and energy. Previous studies have shown that degradation of nitrobenzene involves the reduction of nitrobenzene to nitrosobenzene and hydroxylaminobenzene, followed by rearrangement to 2-aminophenol, which then undergoes meta ring cleavage to 2-aminomuconic semialdehyde. In the present paper, we report the enzymatic reactions responsible for the release of ammonia after ring cleavage. 2-Aminomuconic semialdehyde was oxidized to 2-aminomuconate in the presence of NAD by enzymes in crude extracts. 2-Aminomuconate was subsequently deaminated stoichiometrically to 4-oxalocrotonic acid. No cofactors are required for the deamination. Two enzymes, 2-aminomuconic semialdehyde dehydrogenase and a novel 2-aminomuconate deaminase, distinguished by partial purification of the crude extracts, catalyzed the two reactions. 4-Oxalocrotonic acid was further degraded to pyruvate and acetaldehyde. The key enzyme, 2-aminomuconate deaminase, catalyzed the hydrolytic deamination that released ammonia, which served as the nitrogen source for growth of the organism.